The Representations of Socialist Feminism on Lesley Gore’s You Don't Own Me - Pasopati, Rommel Utungga; Oktavia, Dian; Ayu, Evangelin Rambu; Salsabiyla, Raddine; Andharu, Devito (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This article exposes analysis of socialist feminism through the song of Lesley Gore entitled You Don't Own Me. Popularized in the 1960s, this song conveys the strength of a woman to fight against any dictation and to reject the wishes of men. This is in line with Clara Zetkin’s socialist feminism in which a woman must always be free from any man’s possession. Zetkin bases her thoughts on socialist concepts that emphasize equality between men and women out of any capital accumulation. By using qualitative methods, in the analysis, Gore uplifts women's dignity by rejecting any domestication and dictation done by men. Women must sound their own voices and stand up for their own rights. In conclusion, women are full of uniqueness that must not be reduced as a toy for men. Women are human beings that are never parts of the capital accumulation of men.